Improved Learning Outcomes Problem Solving Problem Fractions Using Polya Strategies: Peningkatan Hasil Belajar Pemecahan Masalah Soal Cerita Pecahan Menggunakan Strategi Polya - sonia yulia friska; Ana Novita Sari (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2020)
This research is motivated by the low learning problem solving in story item reductions with different denominator. This research was aimed at improving the students’ learning achievement in story items of the reduction with different denominator by using Polya strategy. This research was conducted in SDN 09 Bandar Buat Kota Padang. The research subject teacher and the IV grade students were 23 people. research result shows learning outcomes cycle I obtaining an average value of 71,52 and increase in cycle II to 83,18.